(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2021)
Iceland was one of the countries which were hit by the financial crisis in 2008 the most. The entire banking system in Iceland collapsed. In this paper, we discuss the causes of Icelandic downfall. We also focus on the question if the membership in the European Union and euro as a currency could have helped Iceland in this time. Using the case of Ireland, we assume that euro as a currency could have helped Iceland. It is hard to predict what the EU would done in Iceland case because there is no legislation concerning the situation. Comparing the financial crisis in 2008 in Iceland and Ireland, we can see similarities in EU procedures in this crisis with the Corona Crisis. It seems that in the time of global crisis, EU is not efficient and it its decision-making we can see lack of solidarity which increase the Euroscepticism in members countries. Keywords: Financial Crisis in 2008, Iceland, Ireland, European Union, Currency, Banking Collapse, Corona crisis, EU decision-making